An approach to the diagnosis and management of Rome IV functional disorders of chronic constipation. (2nd January 2020) - Aziz, Imran; Whitehead, William E; Palsson, Olafur S; Törnblom, Hans; Simrén, Magnus
ABSTRACT: Introduction: Chronic constipation is highly prevalent, affecting between 10% and 15% of the population. The Rome IV criteria categorizes disorders of chronic constipation into four subtypes: (a) functional constipation, (b) irritable bowel syndrome with constipation, (c) opioid-induced constipation, and (d) functional defecation disorders, including inadequate defecatory propulsion and dyssynergic defecation. The initial management approach for these disorders is similar, focusing on diet, lifestyle and the use of standard over-the-counter laxatives. If unsuccessful, further therapy is tailored according to subtype. Areas covered: This review covers the definition, epidemiology, diagnostic criteria, investigations and management of the Rome IV disorders of chronic constipation. Expert opinion: By adopting a logical step-wise approach toward the diagnosis of chronic constipation and its individual subtypes, clinicians have the opportunity to tailor therapy accordingly and improve symptoms, quality of life, and patient satisfaction.